Effects of magnesium particle size on combustion characteristic of martian ramjet engine. (1st December 2022) - Yang, Qingchun; Wang, Xu; Xu, Xu; Liu, Jiaxun; Yu, Yang
Abstract: Experiments were conducted to determine the typical magnesium particle size effects on the Mg–CO2 Martian ramjet combustion characteristic. It was carried out at a mainstream mass flow rate of 110 g/s and a temperature of 800 K. In this study, two typical particle sizes (25.2 and 64.6 μm) of magnesium particles that are more easily obtainable in the industry were selected. The morphology, composition, and combustion efficiency corresponding to different particle sizes and equivalence ratios (ER) were analyzed. Results indicate that the 25.2-μm magnesium powder has a wider equivalence ratio adaptation range (ER = 0.13–0.27) and yielded less condensed phase deposition compared to 64.6-μm Mg powder. Combustion efficiency of 85.6% was achieved under the aforementioned conditions. Experimental data shows that 15% of the fine magnesium powder participated in the heterogeneous reaction and caused the pulsating combustion, demonstrating a low frequency (roughly 1 Hz) pressure oscillation. The amplitude even reached 14.6% of the chamber pressure. Remarkably, the condensed phase product produced by the small particle size is mainly magnesium oxide, resulting in an obvious agglomeration phenomenon. In contrast, unburned magnesium particles were detected in the combustion products of large magnesium powder due to the longer combustion time of coarse particles. Highlights: Magnesium particle size effects on the combustion characteristic were researched in the Martian ramjet. The fine magnesium powder participated in the heterogeneous reaction and caused the pulsating combustion. The 25.2-μm particle size has a higher combustion efficiency and less condensed phase deposition.